Self-Disclosure Remaja Kota Pontianak melalui Second Account Instagram - Iftinani, Sheila Zalfa; Gelgel, Ni Made Ras Amanda; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2024)
One of social media that is easy to use to express oneself and interact between users is Instagram. Instagram is the third most used social media platform until January 2021 with the majority of users are teenagers. The application has various features, one of them is the multiple account feature which supports self-disclosure. Instagram users usually do self-disclosure in different places. When you have more than one account, Instagram users tend to present themselves differently on each account. Therefore, there is a phenomenon of Instagram second account which is considered as a relatively safe place to express themselves because it only filled with the closest people. Pontianak City was chosen in this study because Kalimantan is one of the regions with a relatively high level of digital literacy and the era of globalization has touched Pontianak City so that it has influenced Pontianak City youth in using Instagram. this study uses a qualitative research method with dramaturgy theory by Erving Goffman where the main account is the front page and the second account is the back stage. The informants of this research involving 4 Pontianak City teenagers consisting of two boys and two girls. The researcher found that there are several reasons and purposes put forward by the informants for using second Instagram accounts and also there are differences in appearance and identify used in each account.